Event Selection Criteria for the 6-Jet Higgs Channel, At JLC - B. MAGALLANES, JINGLE; C. SANCHEZ, ALLISTER LEVI; C. AROGANCIA, DENNIS; C. GOOC, HERMOGENES; M. BACALA, Ph.D., ANGELINA; MIYAMOTO, AKIYA; FUJII, KEISUKE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Higgs boson, the missing piece of the Standurl Model has a chance to be discovered at the Joint Linear Collider (JLC). In order to study this elusive particle and find many of its properties we formulate an event selection criteria that will select the 6-jet Higgs channel through computer simulation using the JLC Study Framework (JSF).